Discrepancy between subjective and objective memory change after epilepsy surgery: Relation with seizure outcome and depressive symptoms - Florian Johannes Mücke; Florian Johannes Mücke; Marc Petrus Hendriks; Marc Petrus Hendriks; Christian Günther Bien; Philip Grewe; Philip Grewe (Frontiers in Neurology, 2022)
Complaints pertaining to memory functioning are among the most often reported cognitive symptoms in patients with epilepsy. However, research suggests a considerable mismatch between patients' perception of memory functioning and the objective performance as measured with standardized neuropsychological tests. Depressive mood might be an important factor in explaining this discrepancy, though other variables have also occasionally been reported as relevant. There are mixed results as to which role these factors play in determining the overall quality of life of patients with epilepsy. The present study aimed to quantify the mismatch between subjective and objective memory functioning by taking into account the dynamic change of these factors as well as depressive symptoms after epilepsy surgery. Moreover, the influencing factors of subjective and objective memory change were investigated as well as their effects on the overall quality of life. Pre- and postoperative data from 78 patients with focal epilepsy were retrospectively analyzed. The results showed that (1) patients with clinically relevant postoperative depressive symptoms underestimate their actual memory performance; (2) for non-seizure-free patients, a postoperative decrease in depressive symptoms was associated with a tendency to underestimate memory decline; (3) the relationship between objective memory change and quality of life is mediated by the factors subjective memory change and depressive mood. Our data demonstrate a quantitative approximation of a pronounced depression-related negative biased self-perception of memory functioning of roughly 1 to 1.5 standard deviations. Moreover, it seems that when patients are relieved of having recurrent epileptic seizures, they may be less influenced by depressive symptoms when judging their memory change. Taken together, our study demonstrates the clinical relevance of incorporating subjective measures of memory functioning and mood that go beyond objective memory performance for the interpretation of how changes in memory functioning may affect patients' quality of life after epilepsy surgery.